Epidemiological survey of oral and maxillofacial complex biopsies: 13 year retrospective study - Antonione Santos Bezerra Pinto; Moara e Silva Conceição Pinto; Ney Soares de Araújo (Brazilian Dental Science)
Objective: To conduct a retrospective study through epidemiological survey of the biopsies of oral cavity performed at the Center of Pathology, Cytology, and Cytopathology– CEPACC in Parnaíba-PI, from 1998 to 2011. Material and Methods: One hundred and thirty-nine referrals and reports were analyzed by evaluating the group and prevalence of oral lesions, anatomical location, and distribution in relation to type, gender, and age. Results: Females (52%) showed the greatest prevalence, observing more cases in the age range of 41 to 60 years. The lip was the preferable location of the analyzed lesions. The groups of the lesions in salivary glands (17%), malignant tumors of epithelial origin, benign tumors of conjunctive origin, premalignant lesions of epithelial origin, and odontogenic cysts were the most common lesions. Considering the isolated lesions, squamous cell carcinoma was the most frequent. We observed a greater preference for salivary gland lesions, although great diversity of clinical cases was found. Conclusion: The reported lesions occurred mostly in adult females and in groups with salivary gland diseases. Keywords Epidemiology; Oral lesions; Biopsy; Oral Pathology; Diagnosis.